COOPERATIVE STRATEGIES IN SECURITY MANAGEMENT (PUBLIC ADMINISTRATION) - Röttinger, Raphael (E-Journal VFU, 2025)
Public security in Germany is facing growing challenges characterised by extremism, terrorism, cyber attacks and organised crime. These threats require a reassessment of the security architecture and the development of co-operative strategies. This study analyses how effective security management can be shaped through interdisciplinary cooperation between public institutions, civil society and security authorities. Case studies such as the GABI project in Bonn and the "Connect" initiative show that co-operation can not only improve objective security, but also the subjective sense of security of the population. At the same time, there are challenges, including communication deficits, legal barriers and a lack of resources, which need to be overcome. The paper concludes with recommendations for the promotion of cooperation structures, integrative strategies and innovative technologies to strengthen the resilience of society and effectively counter future threats.
Keywords: Public administration; co-operative strategies; GABI; public safety; safety management